One money, many countries - Favero, Carlo. Centre for Economic Policy Research (London : Centre for Economic Policy Research, 2000)
This report provides a detailed analysis of the European Central Bank's actions and alerts the public to the main issues raised by the policies pursued by the Bank during its first year. It also provides an assessment of the key concerns in the implementation of European monetary union.
Includes bibliographical references.
Keywords: European Central Bank .; Banks and banking, Central -- Europe; Monetary policy -- European Union countries; International trade; Finance; Taxation